Revealed Preference in President Election 2019 in Padang City West Sumatra Province - Dewi Anggraini, Eka; Karimi, Syafruddin; Indrawari, Indrawari; Ridwan, Endrizal (Opción, 2019)
Preference is the attitude that underlies the choice of consumers in choosing commodities. This attitude is not a genetic character that is carried at birth, but rather formed because of framing, habits, and situations that make con- sumers need to choose a choice. Because the influence of these three factors the resulting options may not reflect consumer preference. Moreover, in mak- ing political decisions that are full of interest, stated preference is a difficult matter to do. However, the revealed preference theory can overcome the issue by observing the community options in the 2019 presidential election in Pa- dang City West Sumatera province. The goal is to reveal voter preferences and associated relationships with it. Data were collected through research poll deployments to explore expected leader characters. There are four characters namely populist, smart, assertive, and humble. The result of research showed the sequence of characters the preferred voters of the candidate 01 was pop- ulist, humble, smart, and assertive. While the sequence of characters that are preferred voters candidate 02 was smart, populist, assertive, and humble. Thus the populist character is the candidate 01 voters’ preference and smart character is the candidate 02 voters’ preference.